Contribution of ROS and metabolic status to neonatal and adult CD8+ T cell activation. - José Antonio Sánchez-Villanueva; Otoniel Rodríguez-Jorge; Oscar Ramírez-Pliego; Gabriela Rosas Salgado; Wassim Abou-Jaoudé; Céline Hernandez; Aurélien Naldi; Denis Thieffry; María Angélica Santana (PLoS ONE)
In neonatal T cells, a low response to infection contributes to a high incidence of morbidity and mortality of neonates. Here we have evaluated the impact of the cytoplasmic and mitochondrial levels of Reactive Oxygen Species of adult and neonatal CD8+ T cells on their activation potential. We have also constructed a logical model connecting metabolism and ROS with T cell signaling. Our model indicates the interplay between antigen recognition, ROS and metabolic status in T cell responses. This model displays alternative stable states corresponding to different cell fates, i.e. quiescent, activated and anergic states, depending on ROS levels. Stochastic simulations with this model further indicate that differences in ROS status at the cell population level contribute to the lower activation rate of neonatal, compared to adult, CD8+ T cells upon TCR engagement. These results are relevant for neonatal health care. Our model can serve to analyze the impact of metabolic shift during cancer in which, similar to neonatal cells, a high glycolytic rate and low concentrations of glutamine and arginine promote tumor tolerance.